Processing and transport of environmental virus samples. - Dahling, D R (1984)
Poliovirus-seeded tap water, conditioned with MgCl2 and passed through virus-adsorbing filters, gave better poliovirus recovery than water identically treated but conditioned with AlCl3. Elution of several filter types with beef extract yielded higher recoveries than did elution with glycine. Seeded samples filtered through various filters and stored showed considerable virus loss in 2 days when stored at 4 degrees C, whereas those stored at -70 degrees C gave stable virus recovery up to 4 days. Additionally, the use of antifoam during the elution process reduced foaming and increased virus recovery by 28%.